2017
DOI: 10.1021/acsami.6b13217
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Tuning of Phase Transition Temperature in VO2 Thin Films on c-Cut Sapphire Substrates via Strain Variation

Abstract: Vanadium dioxide (VO) thin films with controlled thicknesses are deposited on c-cut sapphire substrates with Al-doped ZnO (AZO) buffer layers by pulsed laser deposition. The surface roughness of AZO buffer layers is varied by controlling oxygen pressure during growth. The strain in the VO lattice is found to be dependent on the VO thickness and the VO/AZO interface roughness. The semiconductor-to-metal transition (SMT) properties of VO thin films are characterized and the transition temperature (T) is successf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
56
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 95 publications
(61 citation statements)
references
References 50 publications
5
56
0
Order By: Relevance
“…This reflection seems no relationship with the sapphire itself because no diffraction plane of the sapphire can be observed around this position. The slight peak position shift of the VO 2 film on a substrate can be related to stress and strain of the lattice …”
Section: Resultsmentioning
confidence: 52%
See 3 more Smart Citations
“…This reflection seems no relationship with the sapphire itself because no diffraction plane of the sapphire can be observed around this position. The slight peak position shift of the VO 2 film on a substrate can be related to stress and strain of the lattice …”
Section: Resultsmentioning
confidence: 52%
“…As shown in Figure (a), the matching unit in sapphire (0001) plane are about 2 times larger than the matching unit in the (020) plane of monoclinic VO 2 , 4.570 × 2.851 Å 2 . Therefore, the VO 2 film would be preferred deposited in rutile (011) axis on the sapphire (0001) plane during the thermal deposition process and then became monoclinic (020) axis preferred phase, as reported . This type of lattice matching may be applied to explain the preferred growing of monoclinic (−211) axis near 37.5°.…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…It was concluded that the in-plane tensile strain induced by the interfacial lattice mismatch could modify the electronic structure of VO 2 and the strain relaxed gradually when increased the thickness of the VO 2 film. [30,32,225,226] The local modulation such as atomic defects also affects τ c . Taking the W dopant as an example, it was directly observed on an atomically resolved strain map to induce the anisotropic localized stress in the M phase by the aberration-corrected scanning TEM.…”
Section: Strain Triggered Phase Transition Of Vomentioning
confidence: 99%